Thermo-acoustic cross-talk between cans in a can-annular combustor. (December 2017) - Farisco, Federica; Panek, Lukasz; Kok, Jim BW
Thermo-acoustic instabilities in gas turbine engines are studied to avoid engine failure. Compared to the engines with annular combustors, the can-annular combustor design should be less vulnerable to acoustic burner-to-burner interaction, since the burners are acoustically coupled only by the turbine stator stage and the plenum. However, non-negligible cross-talk between neighboring cans has been observed in measurements in such machines. This study is focused on the analysis of the acoustic interaction between the cans. Simplified two-dimensional (2D) and three-dimensional (3D) equivalent systems representing the corresponding engine alike turbine design are investigated. Thermo-acoustic instabilities are reproduced using a forced response approach. Compressible large eddy simulation based on the open source computational fluid dynamics OpenFOAM framework is used applying accurate boundary conditions for the flow and the acoustics. A study of the reflection coefficient and of the transfer function between the cans has been performed. Comparisons between 2D and 3D equivalent configurations have been evaluated.